Using cash to monitor liquidity - implications for payments, currency demand and withdrawal behavior - Ulf Von Kalckreuth; Tobias Schmidt; Helmut Stix (European Central Bank (ECB), 2011)
Standard transaction cost arguments can only partially explain why the share of cash transactions is still high in many countries. This paper shows that consumers' desire to monitor liquidity is one of the reasons. Consumers make use of a distinctive feature of cash – a glance into one's pocket provides a signal for both the remaining budget as well as the level of past expenses. We propose a theoretical framework which incorporates this feature of cash, and derives implications not only for cash usage as such but also for a broader set of payment-related activities. Survey data from Germany on consumers' payment and withdrawal patterns are used to test these implications empirically. The data are consistent with all theoretical predictions: consumers who need to keep control over their remaining liquidity and who have elevated costs of information processing and storage will conduct a larger percentage of their payments using cash, hold fewer non-cash payment instruments, withdraw less often and hold larger cash balances than other consumers. Such consumers also use payment cards for some transactions; they switch to non-cash payment instruments only at higher transaction values than other consumers, however. Our model provides an explanation of why cash usage has declined only slowly in some countries despite broad diffusion of non-cash means of payment.
Keywords: E41; E58; D12; 330; cash usage; currency demand; Payment behavior; payment cards; payment innovation; Payment instruments; survey data; withdrawal behavior